Hubungan antara Konsep Diri dengan Ide Bunuh Diri pada Mahasiswa di Yogyakarta - Maura Rachel Anisha Damopolii; Zahro Varisna Rohmadani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Students are individuals who are studying at a university, with an important role as Agents of Change. Suicidal ideation refers to the feeling that life is worthless, and tends to occur in individuals with negative self-concepts. This study aims to determine whether there is a relationship between self-concept and suicidal ideation in students in Yogyakarta. This study uses a quantitative descriptive and inferential approach with a simple correlation method. The subjects of this study were 100 active students at universities in Yogyakarta, data collection was carried out online via google forms that measure self-concept and suicidal ideation and distributed via social media, then tested using the classical assumption test, person correlation test and hypothesis test. The results of the study were that there was a significant negative relationship between self-concept and suicidal ideation in students, which was indicated by a t value = 2.272, namely a significant negative relationship between self-concept and suicidal ideation. This finding confirms the importance of paying attention to self-concept in efforts to prevent suicide among students. This study still has several shortcomings, such as the subjects in terms of gender and age are not balanced, namely only at the age of 18-23 years, where students or teenagers start from the age of 18-24 years.